Diversity of Fern and Fern-Allies of Tarai West Forest Division, Ramnagar, Uttarakhand - Joshi, Bhasker; Tewari, Sona; Shukla, B.K.; Srivastava, Anupam (Indian Forester, 2018)
Present paper deals with diversity of Fern and Fern-Allies of Tarai West Forest Division, Ramnagar, Uttarakhand. In the present study 14 species have been collected from the area. Systematic enumeration, morphological characters, India and abroad distribution along with ecological notes have been appendage in each species.